La3B6O13(OH): The First Acentric High‐Pressure Borate Displaying Edge‐Sharing BO4 Tetrahedra. Issue 30 (20th May 2020) - Fuchs, Birgit; Heymann, Gunter; Wang, Xuefei; Tudi, Abudukadi; Bayarjargal, Lkhamsuren; Siegel, Renée; Schmutzler, Adrian; Senker, Jürgen; Joachim‐Mrosko, Bastian; Saxer, Andreas; Yang, Zhihua; Pan, Shilie; et al.
Abstract: La3 B6 O13 (OH) was obtained by a high‐pressure/high‐temperature experiment at 6 GPa and 1673 K. The compound crystallizes in the space group P 21 (no. 4) with the lattice parameters a= 4.785(2), b= 12.880(4), c= 7.433(3) Å, and β =90.36(10)°, and is built up of corner‐ as well as edge‐sharing BO4 tetrahedra. It represents the first acentric high‐pressure borate containing these B2 O6 entities. The compound develops borate layers of „sechser"‐rings with the La 3+ cations positioned between the layers. Single‐crystal and powder X‐ray diffraction, vibrational and MAS NMR spectroscopy, second‐harmonic generation (SHG) and thermoanalytical measurements, as well as computational methods were used to affirm the proposed structure and the B2 O6 entities. Abstract : Sharing is caring : La3 B6 O13 (OH) was obtained via a high‐pressure/high‐temperature route at 6 GPa and 1673 K. The compound represents the first acentric borate displaying the rare feature of edge‐sharing BO4 tetrahedra. SHG measurements reveals a significant signal; further characterizations were carried out by NMR and vibrational spectroscopy, thermoanalytical analysis, and computational methods.